Circuit Simulation for Wind Power Maximum Power Point Tracking with Four Switch Buck Boost Converter - Machmud Effendy, ME; Khusnul Hidayat; Nuralif Mardiyah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Wind turbines have maximum mechanical power at certain wind speeds. Maximum Power Point Tracking (MPPT) is an electronic system capable of extracting maximum wind turbine power. The purpose of this research is to improve wind power efficiency through MPPT wind power design with four switch buck boost converter and Fuzzy control algorithm. Fuzzy control has two inputs are power changes and voltage changes and one output feeding to the pulse width modulation generator to control FSBB. Simulation results with Matlab simulink shows that wind power without MPPT produce 89% power efficiency, wind power MPPT with two switch buck boost converter yield 90% power efficiency and emerging high ripple current. The last simulation of wind power MPPT with FSBB produces the highest efficiency of 91% with low ripple current.